The American College of Rheumatology and the Systemic Lupus International Collaborating Clinics Classification criteria for systemic lupus erythematosus in two multiethnic cohorts: a commentary. (January 2014) - Pons-Estel, GJ; Wojdyla, D; McGwin, G; Magder, LS; Petri, MA; Pons-Estel, BA; ,; Alarcón, GS; ,
The authors offer some comments on the advantages and possible drawbacks of using the SLICC criteria in longitudinal observational studies and clinical trials after applying and comparing them to the ACR criteria in two multinational, multiethnic lupus cohorts.